2017
DOI: 10.1097/mpg.0000000000001568
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Bone Mineral Density in Children With Screening‐detected Celiac Disease

Abstract: Children with screening-detected celiac disease have reduced BMD, lower levels of vitamin D3, higher levels of PTH, and signs of systemic inflammation compared with controls. These differences were not found in celiac disease children on a gluten-free diet, indicating that children with screening-detected celiac disease benefit from an early diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
3
31
0
1
Order By: Relevance
“…7 In fact, some asymptomatic children already had signs of anaemia and poor growth, and others have reported that such patients can suffer from osteopaenia and underachievement. 4,32 Furthermore, although more studies are needed, an early-initiated gluten-free diet might reduce the risk of other autoimmune diseases. 33,34 Although most of our results support childhood screening, certain challenges remain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In fact, some asymptomatic children already had signs of anaemia and poor growth, and others have reported that such patients can suffer from osteopaenia and underachievement. 4,32 Furthermore, although more studies are needed, an early-initiated gluten-free diet might reduce the risk of other autoimmune diseases. 33,34 Although most of our results support childhood screening, certain challenges remain.…”
Section: Discussionmentioning
confidence: 99%
“…3 Supporting early diagnosis, screen-detected children may already have advanced disease and a subsequent risk of permanent complications such as impaired growth and reduced bone accrual. [4][5][6][7] Delaying diagnosis until later adulthood predisposes to even more severe maladies, including osteoporotic fractures and refractory coeliac disease. 8 Counterweighting the benefits of screening is the burden of demanding treatment.…”
Section: Introductionmentioning
confidence: 99%
“…). Also, apparently asymptomatic patients may already have advanced histological damage and thus increased risks for complications such as osteopenia, underachievement and impaired growth (Table ). On the other hand, the evidence about the risks for severe long‐term complications, such as infertility, osteoporotic fractures, malignancies and increased mortality, in unrecognised coeliac disease patients is controversial .…”
Section: Consequences Of a Missed Or Delayed Coeliac Disease Diagnosismentioning
confidence: 99%
“…Timely diagnosis of celiac patients is important in preventing long-term complications such as osteopenia, growth retardation, infertility and malignancies associated with untreated disease (11,12).…”
Section: Introductionmentioning
confidence: 99%